A Component-Oriented Support for Hierarchical MPI Programming on Multi-Cluster Grid Environments - Mathias, Elton; Baude, Francoise; Cave, Vincent; Maillard, Nicolas (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2007)
In this paper, we present a proposal for hierarchical MPI programming through some intuitive extensions to the MPI standard that may help users to develop non-embarrassingly parallel grid applications in a topology- aware manner. Afterwards, we present the design of such a support based upon a component model suited to grid computing (the EU CoreGRID grid component model - GCM - and its implementation in the ProActive grid environment) to handle inter-cluster and group communications. The usage of such components to handle high-level data distribution, parallelism and synchronization seems to be the most adequate technology to support MPI primitives in multi-cluster grids as they provide a built-in support to the encapsulation of native code, collective interfaces, tunneling of communications and a hierarchical and adaptable structure. The preliminary results have shown that the overhead is not negligible, but within the expected range. However we can expect the benefits to applications to bypass the generated overhead.